Efektifitas Penggunaan QR Code Pada Form Booking Ruangan Multimedia Di LKC Binus Kampus Kijang : The Effectiveness of Using QR Codes in Multimedia Room Booking Forms at LKC Binus Kijang Campus - Dede Arafat (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
The advancement of digital technology has encouraged educational institutions to adopt service systems that are more efficient and user-friendly. The Library and Knowledge Center (LKC) at Binus Kijang Campus provides multimedia room facilities for academic and student organization activities. In 2025, LKC began implementing a QR Code–based booking system to replace the previous manual process. This study aims to analyze the effectiveness of using QR Codes in the multimedia room booking form by examining four key aspects: ease of use, time efficiency, data accuracy, and user satisfaction. A quantitative research approach was applied through a survey of 100 active students at Binus Kijang Campus. The results indicate that the QR Code system improves booking efficiency by 72%, increases data accuracy by 65%, and achieves a user satisfaction rate of 85%. In conclusion, the implementation of the QR Code–based booking system is effective in supporting LKC operations and enhancing the overall user experience.